Modifying the conductive properties of poly(3,4-ethylenedioxythiophene) thin films in green solvents - Hou, Bin; Ma, Chuao; Li, Sidi; Liu, Hongliang (Frontiers in Chemistry, 2022)
With the rapid development of flexible electronic devices, flexible transparent conductive materials acted as the charge transport layer or electrical interconnect in the devices are of great need. As one of the representative conductive materials, poly(3,4-ethylenedioxythiophene) (PEDOT) has received more and more attention due to its high transparency in the visible region, good flexibility, especially the tunable conductivity. In order to achieve high conductivities, various of effective approaches have been adopted to modify the PEDOT thin films. However, some strategies need to be carried out in hazardous solvents, which may pollute the environment and even hinder the application of PEDOT thin films in emerging bioelectronics. Therefore, in this mini review, we focus on the discussion about the modification methods for PEDOT thin films in green solvents. According to the source of PEDOT, the modification methods of PEDOT thin films are mainly described from two aspects: 1) modification of in-situ PEDOT, 2) modification of PEDOT complex with poly(styrenesulfonic acid) (PEDOT:PSS). Finally, we conclude with the remaining challenges for future development on the PEDOT thin films prepared by green methods.